Effectiveness Of Recess Implementation By Regional People's Representative Council Members In Absorbing Public Aspirations: A Case Study Of Musi Rawas Regency: Efektivitas Pelaksanaan Reses Anggota Dewan Perwakilan Rakyat Daerah Dalam Menyerap Aspirasi Masyarakat: Studi Kasus Kabupaten Musi Rawas - Ferawati; Alexsander; Rahiman Dani (Gayaku Publisher, 2026)
This study aims to analyze and evaluate the effectiveness of the Regional People's Representative Council (DPRD) members' recess in Musi Rawas Regency in absorbing community aspirations, as well as to identify the constraints in its implementation. Recess is a crucial instrument in the representative democratic system that serves to facilitate political communication between representatives and their constituents, while also providing the basis for regional development policy formulation. This study employs a descriptive qualitative approach. Data collection was carried out through in-depth interviews, participatory observation, and documentation studies. Research informants were determined using purposive sampling techniques involving DPRD members, DPRD Secretariat officials, and community leaders. Data analysis used an interactive model, which includes data reduction, data display, and conclusion drawing. The results indicate that the effectiveness of the DPRD Musi Rawas recess implementation falls into the moderately effective category. Of the four effectiveness indicators analyzed, two indicators showed optimal performance: cost calculation accuracy, which complied with regulations, and timeliness, which aligned with the session periods. However, the other two indicators still require optimization: goal achievement (not all community aspirations can be realized due to APBD limitations and clashes with priority scales) and target accuracy (community participation remains low due to the lack of transportation funds affecting attendance enthusiasm). The conclusion of this study emphasizes the need for reform in post-recession aspiration management and an increase in community empowerment budget allocations to enhance public participation.